A business-cycle model with a modified cash-in-advance feature, government sector and one-period nominal wage contracts: the case of Bulgaria - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance, 2020)
A business-cycle model with a modified cash-in-advance feature, government sector and one-period nominal wage contracts: the case of Bulgaria